WHEN QUIZWHIZZER IS USED EFFECTIVELY AT SMAN 1 BLITAR IN THE TENTH GRADE TO ENHANCE STUDENTS’ READING COMPREHENSION - Agung Cahyono, Muh. Felix; Puspita Sari, Hesty; Sutanti, Nita; Supriyono (Universitas Islam Balitar, 2024)
This research uses Quiz Whizzer to determine the effectiveness of Quiz Whizzer in improving the reading comprehension of recount text from 37 students in class X5 of SMAN 1 Blitar. The researcher wants to know the effectiveness of Quiz Whizzer in improving reading comprehension of recount text. The things the researcher wants to research include; finding the main idea, synonyms and antonyms, references, implied and explicit meaning, and concluding the reading text. The results show a significant increase in students' reading comprehension of recount text, this is proven by the average of 74.74 increasing to 83.84. Therefore, it can be recommended that teachers use Quiz Whizzer as an alternative learning medium as a medium for teaching and improving students' abilities.